Development of numerical model for predicting the characteristics of Ni–SiC nano composite coatings on AISI 1022 substrate. (15th May 2019) - Natarajan, P; Jegan, A; Sankar Ganesh, S
Abstract: The strength of nano coatings predominantly depends on the selection of optimum combination of input parameters. This problem can be solved by developing an empirical relationship between input parameters to predict microhardness (MH), average surface roughness (Ra), specific wear rate (Ws) and co-efficient of friction (CoF) of the pulse electroplated coating by response surface methodology (RSM). In this paper an attempt has been made to optimize the electroplating process parameters of Ni–SiC nano coating using Grey-RSMapproach. This experiment highlights the use of RSM by designing the three factor three level central composite design. The Ni–SiC nano coating was deposited on AISI 1022 low carbon steel substrates under pulse current electroplating technique using nickel watts bath by varying input parameters such as frequency (Hz), duty cycle (%) and current density (A/Cm 2 ). The optimum electroplating parameter was obtained through grey relational analysis (GRA). The prediction of optimum nano composite coating parameter is found at frequency 10 Hz (F1), duty cycle 10% (D1) and current density 0.2 A Cm −2 (C2), then confirmation experiment is performed to verify the optimum process parameter condition. The influences of those optimized coating parameters over the microstructure, morphology, coating thickness, EDAX, x-ray diffraction and wear rate of Ni-nano SiC composite coatings were also investigated.